The fourth estate and the Constitution : freedom of the press in America - Powe, L. A. Scot. (Berkeley : University of California Press, 1991)
In 1964 the Supreme Court handed down a landmark decision in New York Times v. Sullivan guaranteeing constitutional protection for caustic criticism of public officials, thus forging the modern law of freedom of the press. Since then, the Court has decided case after case affecting the rights and restrictions of the press, yet little has ben written about these developments as they pertain to the Fourth Estate. Lucas Powe's essential book now fills this gap. Lucas A. Powe, Jr., a legal scholar specializing in media and the law, goes back to the framing of the First Amendment and chronicles the two main traditions of interpreting freedom of the press to illuminate the issues that today ignite controversy: • How can a balance be achieved among reputation, uninhibited discussion, and media power? • Under what circumstance can the government seek to protect national security by enjoining the press rather than attempting the difficult task of convincing a jury that publication was a criminal offense? • What rights can the press properly claim to protect confidential sources or to demand access to information otherwise barred to the public? • And, as the media grow larger and larger, can the government attempt to limit their power by limiting their size? Writing for the concerned layperson and student of both journalism and jurisprudence, Powe synthesizes law, history, and theory to explain and justify full protection of the editorial choices of the press. The Fourth Estate and the Constitution not only captures the sweep of history of Supreme Court decisions on the press, but also provides a timely restatement of the traditional view of freedom of the press at a time when liberty is increasingly called into question.
Frontmatter -- Contents -- Preface -- Introduction -- Part One: Traditions -- Overview -- 1. The Framers and the First -- 2. Freedom of the Press in Times of Crisis -- 3. Freedom of the Press from Times to Times -- Part Two: Issues -- Overview -- 4. Libel -- 5. Prior Restraints -- 6. Access to Sources and Information -- 7. Antitrust -- Part Three: Models -- Overview -- 8. The Right to Know -- 9. The Fourth Estate -- Conclusion -- Notes -- Index
Includes bibliographical references (pages 299-343) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Freedom of the press -- United States; Liberté de la presse -- États-Unis.; LAW -- Constitutional; LAW -- Public; Freedom of the press; United States; Freedom of the press; United States; Libel; Freedom of information; Overseas item; Prior restraints